2019
DOI: 10.1186/s12903-019-0797-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluate five different diagnostic tests for dry mouth assessment in geriatric residents in long-term institutions in Taiwan

Abstract: Background Residents in long-term care (LTC) institutions require care plans to effectively resolve dry mouth. Simple and easily comprehensible dry mouth indices must be developed to assist care professionals in determining dry mouth among residents. Therefore, this study aim of the study was to evaluate five different diagnostic tests for dry mouth assessment. Methods A total of 568 residents were recruited from several LTC institutions in central Taiwan. The research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 61 publications
0
9
0
3
Order By: Relevance
“…OHIP-7—a validated Mandarin version of OHIP in NC_TLSA ( 31 ), which had been used in a previous study ( 32 , 33 )—surveys individuals' experiences related to teeth or denture problems in the past 12 months at the time of the interview through seven questions: (1) “Have you ever been aware of teeth or dentures problems?”, (2) “Have you ever been interrupted in a meal because of teeth or dentures problems?”, (3) “Have you ever experienced discomfort while eating because of teeth or dentures problems?”, (4) “Have you ever had difficulties with concentration because of teeth or dentures problems?”, (5) “Have you ever experienced difficulties with pronunciation because of teeth or dentures problems?”, (6) “Have you ever confronted difficulties with performing daily life because of teeth or dentures problems?” and (7) “Have you sensed taste deterioration because of teeth or dentures problems?”. Each survey question was rated on a 5-point Likert scale (never = 0, rarely = 1, occasionally = 2, often = 3, and very often = 4).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…OHIP-7—a validated Mandarin version of OHIP in NC_TLSA ( 31 ), which had been used in a previous study ( 32 , 33 )—surveys individuals' experiences related to teeth or denture problems in the past 12 months at the time of the interview through seven questions: (1) “Have you ever been aware of teeth or dentures problems?”, (2) “Have you ever been interrupted in a meal because of teeth or dentures problems?”, (3) “Have you ever experienced discomfort while eating because of teeth or dentures problems?”, (4) “Have you ever had difficulties with concentration because of teeth or dentures problems?”, (5) “Have you ever experienced difficulties with pronunciation because of teeth or dentures problems?”, (6) “Have you ever confronted difficulties with performing daily life because of teeth or dentures problems?” and (7) “Have you sensed taste deterioration because of teeth or dentures problems?”. Each survey question was rated on a 5-point Likert scale (never = 0, rarely = 1, occasionally = 2, often = 3, and very often = 4).…”
Section: Methodsmentioning
confidence: 99%
“…OHIP-7-a validated Mandarin version of OHIP in NC_TLSA (31), which had been used in a previous study (32,33)-surveys individuals' experiences related to teeth or denture problems in the past 12 months at the time of the interview through seven questions: (1) "Have you ever been aware of teeth or dentures problems? ", (2) "Have you ever been interrupted in a meal because of teeth or dentures problems?…”
Section: Dependent Variablesmentioning
confidence: 99%
“…5 Xerostomia can also lead to conditions such as burning mouth that compromises chewing and swallowing, bringing consequences to health in general and compromising the quality of life. 4,6 For its evaluation, some studies use salivary flow measurement, but a study conducted in 2017 showed that hyposalivation, a complaint usually associated with xerostomia, is not always true since most patients with dry mouth sensation had normal salivary flow. (70%) 7 Another means of assessing xerostomia is the Thomson questionnaire created in 1999, known as the "Xerostomia Inventory", consisting of 11 items designed to assess various dry mouth sensation situations, with five response options ranging from one to five.…”
Section: Introductionmentioning
confidence: 99%
“…This fact, when observed in the oral cavity, on average from the 7th to the 10th day after the administration of chemotherapy, presents a predisposition to the appearance of dry mouth and oral infections such as candidiasis, in addition to halitosis, the appearance of lesions, burning mouth, difficulties in chewing, swallowing and speech, as well as decreased taste. All of this has consequences for general health, such as poor nutrition, problems in social relationships and sleep, compromising quality of life (5,(7)(8)(9) .…”
Section: Introductionmentioning
confidence: 99%